The Many Paths of Change in International Law - Krisch, Nico; Yildiz, Ezgi (Oxford University Press, 2023)
How does international law change? How does it adapt to meet global challenges in an accelerated social and political context? The question is crucial for any account of international law, but it is not very well understood. This interdisciplinary volume traces drivers, conditions, and consequences of change across the different fields of international law and paints a complex and varied picture very much in contrast with the relatively static and uniform imagery in most existing accounts. It highlights the social dynamics through which different areas and institutional contexts have generated their own pathways, with different constellations of actors and authorities that condition how smoothly and speedily change proceeds. The volume presents a theoretical framework for understanding this dynamism, and its chapters explore the strategies, forms, and forces behind the many paths of change they encounter. They take into view the politics of precedent and legal restatements, they look at populist and authoritarian challenges and their effects, and they trace change in response to contestation and non-compliance. They also highlight how states are at times marginalized in change processes-and how change may take other forms when international law itself proves too inflexible. Overall, the volume offers a fascinating account of an international legal order in flux-with a degree of dynamism not captured through traditional doctrinal lenses-and helps situate change processes and their varied implications in international law and politics.